A type of 'inverseness' of certain distributions and the inverse normal distribution - Tlakula, Stanley Nkhensani (University of Limpopo, 1978)
Refer to the document
Thesis (M. Sc. (Mathematical Statistics)) -- University of the North, 1978
Keywords: Inverseness; Inverse normal distribution; Inverse Gaussian distribution; Distribution (Probability theory)